Model Komunikasi dalam Membangun Jiwa Kewirausahaan Pemuda di Kota Medan - Alvira Wiabda Sari Tambunan; Habibina Menatri (Al-Balagh : Jurnal Komunikasi Islam, 2022)
The Influence of Communication Models in Building Youth Entrepreneurial Spirit in Medan City. Thepurpose of this journal which discusses the influence of communication models in building the entrepreneurial spirit of youth in the city of Medan is to explain how to convey or inform about buildingand developing an entrepreneurial spirit for youth in the city of Medan. This study uses the method of understanding or observing the area around the city of Medan as a data collection process. The techniqueof analyzing or observing is using sequential learning methods by analyzing a problem. The results showed that the way of entrepreneurship communication, selfdebriefing, and actions in entrepreneurship had aclear effect on the performance of small businesses in developing businesses. It can be seen that the formation of small business performance must be able to take into account the large variables of entrepreneurship, entrepreneurship provision, and actions in entrepreneurship. The impact for research is that we as educators must be extra in building the character of the soul of young people in improving how to make them have a creative soul to build an entrepreneurial spirit.